2017
DOI: 10.7287/peerj.preprints.2824v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linearization improves the repeatability of quantitative Dynamic Contrast-Enhanced MRI

Abstract: 2We studied the effect of linearization on the repeatability of the Tofts and reference 3 region models (RRM) for Dynamic Contrast-Enhanced MRI (DCE MRI). We compared the 4 repeatabilities of these two linearized models, the standard non-linear version, and semi-5 quantitative methods of analysis. to estimate K trans , while LRRM and NRRM were used to estimate K trans relative to muscle 13 (R Ktrans ). Repeatability was assessed by calculating the within-subject coefficient of variation 14 (wSCV) and the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Given that repeatability not only depends on the choice of AIF, but, for example, also on the model, field strength, acquisition protocol, and location of ROI, it is difficult to compare our wCV data directly to existing literature. However, in general, the reported wCV of K trans in ROIs is higher than what we observed for K trans obtained with AIF COMPLEX (range, 12.5–57%) . Rata et al reported a lower wCV of 7.5% when using a population AIF in a group of patients with abdominal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Given that repeatability not only depends on the choice of AIF, but, for example, also on the model, field strength, acquisition protocol, and location of ROI, it is difficult to compare our wCV data directly to existing literature. However, in general, the reported wCV of K trans in ROIs is higher than what we observed for K trans obtained with AIF COMPLEX (range, 12.5–57%) . Rata et al reported a lower wCV of 7.5% when using a population AIF in a group of patients with abdominal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The DCE/IVIM maps are retrieved on the reconstructed signals with HOTVs. We implement a linear DCE solver to significantly boost the speed of parameter estimation while preserving the consistency and repeatability against initial estimations [55,56,57]. A Segmented-Unconstrained algorithm, which is likely the most frequently used algorithm in IVIM analysis [58,59], is adopted in our demonstration section below.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we implemented the linear leastsquares method to acquire the PK parameters. [56,57]. This method is preferred to the conventional nonlinear least-squares method [1], because it is faster and it does not require initial estimation, and has no local optima problems.…”
Section: Computation Of the Kinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Subsequently, we implemented the linear least-squares method to acquire the PK parameters. 25,26 This method is preferred to the conventional nonlinear least-squares method 24 , because it is faster and it does not require initial estimation, and has no local optima problems.…”
Section: Computation Of the Kinetic Modelmentioning
confidence: 99%